Particle Swarm Optimization algorithm for facial emotion detection - Ghandi, B.M.; Nagarajan, R.; Hazry, Desa, Prof. Madya Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/